Floriography / Choo Kim Fong and Syarifah Nuriwana Izzati Hasmadi - Kim Fong, Choo; Hasmadi, Syarifah Nuriwana Izzati (Academy of Language Studies, 2023)
Floriography is an e-book that briefly introduces the language of flowers as well as endangered or extinct flowers. It was created to raise awareness about the issue of endangered or extinct flowers, as well as to learn about the flower language. One of the objectives of this book is to encourage people to learn more about flowers. This book contains a mix of information focusing on endangered or extinct flower species as the main contents of the book and flower language to attract the readers' attention and make their reading session more fun and interesting. This e-book can also be used to raise awareness about the issue of endangered flower species and their importance to ecosystems. A survey was conducted among the general public, and the results show that almost all respondents are interested in this e-book and want to know more about its contents. This e-book differs from others in that it discusses the language and meaning of flowers without addressing the issue of endangered or extinct flower species. The publication of this e-book provides an opportunity to raise awareness of the importance of flowers to ecosystems and to increase flower knowledge among people of all ages.